Divergence of the aerobactin iron uptake systems encoded by plasmids pColV-K30 in Escherichia coli K-12 and pSMN1 in Aerobacter aerogenes 62-1. - Waters, V L (1988)
Although the aerobactin-mediated iron uptake system has been characterized genetically in Escherichia coli, the siderophore aerobactin was chemically characterized after purification from culture supernatants of Aerobacter aerogenes 62-1, a member of the Klebsielleae. We have cloned and mapped the genes encoding the aerobactin system genes of A. aerogenes 62-1 and begun characterization of the relevant proteins and enzymatic activities of this plasmid-mediated aerobactin system. Published chemical data indicate that the siderophore aerobactin of E. coli is the same molecule as the aerobactin of Aerobacter aerogenes 62-1, but we have found that both the genes and the complement of proteins making up the biosynthetic enzymes in the two systems have diverged. In contrast, the outer membrane receptors for ferric aerobactin of the two systems showed immunologic cross-reactivity, were of the same molecular size (74 kilodaltons), and were encoded by homologous DNA sequences.